Electrolyte Disorders Associated with Piperacillin/Tazobactam: A Pharmacovigilance Study Using the FAERS Database - Heenam Seo; Eunyoung Kim (MDPI AG, 2023)
Electrolyte disorders (EDs) can disrupt normal bodily functions and lead to life-threatening complications. We evaluated whether piperacillin-tazobactam (TZP), a widely used antibiotic for moderate-to-severe infections, is associated with electrolyte imbalances via a disproportionality analysis of a self-reporting pharmacovigilance database. We searched The US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) from 2004 to 2018 for EDs related to TZP and calculated three data-mining indices-the proportional reporting ratio (PRR), the reporting odds ratio (ROR), and the information component (IC)-compared to all other drugs. Signals were defined when one of the three criteria of the indices was met. For the signals detected in the initial analysis, further disproportionality analyses in relation to other penicillins were conducted using the same method. A total of 9829 reports related to TZP with 36,207 TZP-adverse event pairs were retrieved. Among 10 EDs, hypokalemia was detected as the only significant signal (PRR 2.61; ROR 2.61, 95% CI: 2.17-3.14; IC 95% lower CI: 1.11) compared to all other drugs. Compared with other penicillins, hypokalemia remained a significant signal for TZP using IC (95% lower CI: 0.26). In conclusion, TZP was significantly associated with hypokalemia.